REDUPLIKASI DAN KATA MAJEMUK DALAM BAHASA MANGGARAI DIALEK KOLANG DI KABUPATEN MANGGARAI BARAT - Hendrik Jehane (Jurnal Lazuardi, 2021)
The Manggarai language, Kolang dialect is one of the dialects included in the Manggarai S > H dialect group (Verheijen, 1930). The S > H dialect group is still not widely known by the Manggarai community in general and by researchers in particular. It is different from Central Manggarai dialect group which is known and understood by most Manggarai people because of its function and role as the standard Manggarai language. Therefore, Manggarai S > H dialect group needs to be researched and introduced through scientific articles to make it more widely known. The research problems are: (1) What is the form and meaning of reduplication in the Manggarai language, Kolang dialect ?; (2) What is the form and meaning of the compound word in the Manggarai language, Kolang dialect? The objectives of this study were: (1) to describe the form and meaning of reduplication in the Manggarai language, Kolang dialect; (2) to describe the form and meaning of the compound word in the Manggarai language, Kolang dialect. The research method used in this research is descriptive method, because the data needed is the language data used by the speaking community in day-to-day communication between speakers. The research results are as follows. (1) The form of the Manggarai language, Kolang dialect reduplication consists of two main types, namely: (1) type I is reduplication without changes in phonemes and (2) and type II is reduplication with changes in phonemes. The meaning of reduplication consists of five types, namely: (1) to state intensive (really); (2) states an iterative meaning (many times); (3) states the meaning of the group; (4) states the meaning of deintensive (not really); (5) states the plural meaning; and (6) states the meaning of exaggeration. The compound word in the Manggarai language, Kolang dialect consists of two types, namely coordinative compound words and subordinative compound words. Coordinative compound words in the Manggarai language, Kolang dialect are less productive when compared to subordinative compounds. There is only one type of coordinative compound words, namely the category of nouns and the constituents consist of nouns (N + N = N). Subordinative compound words are more productive, consisting of seven types.